Perawatan Kesehatan Reproduksi pada Perempuan di Era New Normal - Ningsih, Ratna; Jaya, Herawati; Amin, Maliha; Kumalasari, Intan (Pusat Penelitian dan Pengabdian kepada Masyarakat, Politeknik Kesehatatan Kemenkes Palembang, 2021)
The Covid-19 pandemic has reduced access to reproductive health services and limited socialization and health education during social or physical distancing. The government was gradually implementing the new norm era, we still have to be vigilant and follow health protocols, which in principle are clean and healthy living behavior by means of communication as a medium for sharing information/health education. The aim was to improve and change behavior, as well as women's independence regarding reproductive health. The method of activity was to provide education about reproductive health care for women in the new normal era, through online seminars. The results obtained good knowledge of pre-test 61%, post-test 90%, less knowledge of pre-test 39%, post-test 10%, means that the health care education has an effect on improving health. Keywords: Reproductive Health Care, Women, New Normal